Factors associated with relapse among mentally ill patients attending military mental health clinics (International Journal of Scientific Research and Management (IJSRM), 2022)
Objectives: To assess the prevalence and factors contributing to relapse among mentally ill patients attending military mental health clinics. Method: A cross sectional study was conducted on patients attending military mental health clinics at King Hussein Medical City, Princes Aisha Center, Prince Hashim Hospital and Prince Rashid Hospital. Socio-demographic data questionnaire, internalized stigma of mental illness scale (ISMI), medication adherence scale (MMAS-8), the list of threatening events questionnaire (LTE-Q), oslo’s three items social support scale (OSSS-3) and the alcohol, smoking, and substance involvement screening test (ASSIST-3.0) were utilized for data collection. Data were analyzed using statistical package for social sciences (SPSS) version 22. Results: A total of 311 patients with mental illnesses were included in the study. Prevalence of relapse was 37.3%. Relapse was significantly associated with unemployment (OR = 1.84, 95% CI: 0.92 - 2.63), duration of diagnosis more than 5 years (OR = 2.42, 95% CI: 1.39 – 3.73), severe internalized stigma (OR = 3.12, 95% CI: 1.75 – 4.87) and low adherence to medication (OR = 2.14, 95% CI: 1.54 – 3.89). Conclusion: Around one third of the study participants had relapsed. Unemployment, duration of diagnosis more than 5 years, severe internalized stigma and low adherence to medication were significant predictors for relapse. Researchers suggest the need for future interventional studies focused on modifiable predictors of relapse such as stigma, employment, and medication adherence.